A94 RECURRENT HEPATOCELLULAR CARCINOMA: EVALUATION OF 8 POST-TRANSPLANT SCORING SYSTEMS. (26th February 2020) - Aziz, S; Qumosani, K; Teriaky, A
Abstract: Background: Recurrence of hepatocellular carcinoma (HCC) after liver transplantation is a major cause of morbidity and mortality. It is well known that there is a discordance between pre-transplant imaging and post-transplant pathology that affect risk of recurrence. Several risk assessment tools have been developed, although to date, there is no widely accepted tool to predict HCC recurrence. Aims: The aim of the current study is to determine which pathologic risk assessment score has the best predicative ability. Methods: We retrospectively evaluated 152 patients over a twelve-year period that underwent liver transplantation for HCC. Using explanted pathology reports, each patient was stratified according to the pathologic risk score and followed over time for HCC recurrence. We evaluated eight pathologic risk scores and determined predictive ability by assessing the area under the receiver operating characteristic curve (AUROC). Results: Out of 152 consecutive liver transplants for HCC, recurrence occurred in 21 patients (14%) with a mean follow-up of 59.5 months. 54% of patients were within Milan criteria prior to transplant. According to explant pathology, microvascular invasion was seen in 16% of patients, with majority of the tumors being moderately differentiated (48%), tumor size ≥ 3cm (52%), and 26% of tumors in both lobes of the liver. Preliminary data suggests that the Parfitt et. al score has the best predictive ability, with 60% of recurrence occurring in those considered high-risk. Further assessment via AUROC will be required to confirm the preliminary data. Conclusions: Preliminary data suggests the Parfitt et al. score may have the best predictive ability to detect recurrence. This risk assessment tool can help tailor a surveillance strategy for early detection or early adjuvant therapy to improve long-term survival. Funding Agencies: None